FACTORS INFLUENCING THE ATTITUDE OF STUDENT TEACHERS AT THE FACULTY OF EDUCATION, PHRANAKHON SI AYUTTHAYA RAJABHAT UNIVERSITY, REGARDING VOLUNTEER ACTIVITIES AT THE BORDER PATROL POLICE SCHOOL - Wiwanthamongkhon, Phatsakon; Thangjai, Warisa (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
This research aimed to determine factors influencing the attitudes of student teachers at the Faculty of Education, Phranakhon Si Ayutthaya Rajabhat University, regarding volunteer activities at the Border Patrol Police school and to provide a model for forecasting the attitudes of student teachers at the Faculty of Education, Phranakhon Si Ayutthaya Rajabhat University regarding volunteer activities at the Border Patrol Police school. The sample comprised 34 student teachers who had participated in volunteer activities at Perayanukroh 1 Border Patrol Police school in Sa Kaeo province, using accidental sampling. The research paradigm is based on quantitative research and The tool used to collect the data was a questionnaire. The statistics employed to analyze the data were the frequency, percentage, mean, and standard deviation, and statistical methods comprised a t-test, one-way analysis of variance, and multiple regression analysis. There were no differences in attitude regarding volunteer activities in the Border Patrol Police school among the student teachers regarding their gender, field of study, and academic year. The results of a multiple regression analysis indicate that the form of the volunteer activity, the desirable characteristic, and the benefit of participating statistically significantly influenced the attitude regarding volunteer activities at the 0.050 level. Moreover, the desirable characteristic and the attitude regarding volunteer activities had a positive linear relationship, with the desirable characteristic causing a variation of 55.200% in the attitude regarding the volunteer activities. The results can be used as a guideline for volunteer activity development by focusing on increasing. the desirable characteristic of the student teachers regarding other volunteer activities.